Training progression for younger age group swimmers - Pyne, D. (2004)
For the younger age group swimmers still developing their skills and techniques, the physical conditioning (or fitness training program) is an important but secondary consideration. As the age group swimmer matures the emphasis and time commitment to the training program naturally increases. Even at the beginner level, the training program normally consists of both shorter faster intervals (speed work) and longer slower intervals (endurance work).